Singing For Frog Plain: Representing Canadian/Metis Relations through Falcon’s Songs - Giroux, Monique (Ethnologies, 2015)
Pierre Falcon is the earliest known Metis composer. Born in 1793 in Fort La Coude (Elbow Fort) in what is now west-central Manitoba, his adult life spanned the “Golden Years” (Shore 2001) of the western Metis nation. Known as the Bard of the Prairies, Falcon’s songs drew on events of local importance during this period, providing a means to remember and share Metis history, and to solidify a sense of Metis nationalism. Beginning in the late-1800s historians, novelists, folklorists, journalists, and musicians began turning their attention to Falcon, resulting in a strikingly large number of popular and academic references to his life and songs. While these references are varied, together they tell a story about the relationship between Canada and the Metis Nation. On the one hand, references to Falcon often draw from, and in fact help create, images of the Imaginary Indian (Francis 1992). Yet on the other hand, many references to Falcon erase his Indigeneity, or blend his Metis identity seamlessly into a Franco-Manitoban, or western Canadian identity. These seemingly contradictory representations, as I will argue in this paper, ultimately point to the ambiguous positioning of Metis people as Indigenous peoples, and speak to an obsession with mixed-ness that denies the Metis their full and authentic Indigeneity.